Atomic bond-breaking behaviour during grain boundary fracture in a C-segregated Fe grain boundary. (3rd August 2017) - Miyazawa, Naoki; Hakamada, Masataka; Mabuchi, Mamoru
Abstract: First-principles fully relaxed tensile tests were performed on a C-segregated Fe Σ3 (1 1 1)/[ ] symmetrical tilt grain boundary (GB) to investigate the breaking behaviour of C–Fe bonds during tensile straining. Fe atoms around a C atom moved obliquely to the tensile direction, and C–Fe bonds stretched in the tensile direction without premature bond-breaking. Analyses of the electronic states during deformation showed that a variation in the charge density at the bond critical point was much larger for the C–Fe bond than for the P–Fe bond and that the C atom exhibited larger variations of s and p states involved in the covalent-like characteristics than the P atom. It is suggested that these lead to a high mobility of the C–Fe bonds. On the other hand, first-principles shear tests on the Fe GB imply that C-segregated Fe GB toughening is not associated with increased crack blunting by dislocation emission.